Regulation of osteogenesis of human amniotic mesenchymal stem cells by sodium butyrate. (14th January 2018) - Fan, Xiaoting; Li, Lei; Ye, Zhaoyang; Zhou, Yan; Tan, Wen‐Song
Abstract: Human amniotic membrane‐derived mesenchymal stem cells (hAMSCs) draw great interests for regenerative medicine due to convenient availability and low immunogenicity. However, suboptimal culture conditions limit their application. In recent years, small molecules have proven powerful in regulating stem cell fates and can be applied to stimulate their function. In the present study, the impacts of sodium butyrate (NaBu), a histone deacetylase inhibitor (HDACi), on hAMSCs were investigated. It was shown that NaBu at a low concentration inhibited cell proliferation by arresting cell cycle at G0/G1 rather than inducing apoptosis. When NaBu was supplemented at a concentration of <1.0 mM for 3 days during osteogenic induction, significantly more mineralized nodules were generated and the expression of osteogenesis‐related genes ( ALP, Runx2, Opn, and Ocn ) and proteins (Col1a1, OPN, OCN, Runx2, and TAZ) were both significantly enhanced. However, a higher concentration (1.0 mM) and longer exposure time (14 days) of NaBu showed no such effects, which may be partially attributed to both the increased expression of histone deacetylase 8 (HDAC8) and reduced level of H3K9‐Ace, thus leading to the transcriptional inhibition during osteogenesis. Further, it was indicated that ERK might be involved in the stimulatory effects of NaBu. These findings may be helpful to develop an efficient culture process for hAMSCs towards bone regeneration.